The Motion and Deposition of Small Particles in The Human Lung Acinus, Part A: Micron-size, Infinitely Long Airway - Vanunu, Yakir; Haber, Shimon (British Journal of Healthcare and Medical Research, 2023)
A simple geometrical model of the human lung acinus is investigated. The goal is to get a preliminary insight of the deposition of various size particles. The model comprises of micron- size spherical particles suspended in air, moving inside micron-size, infinitely long pipes. The particle motion is affected by gravity, fluid convection and Brownian motion. Simulations were performed for a 360 mm diameter pipe, a typical size of airways in the human lung acinus. Applying a MATLAB program, it is found that the motion of small particles, (10-9 ¸ 10-8 m) in diameter, is mainly controlled by diffusion, medium size particles (10-7 ¸ 10-6 m) are mainly affected by fluid convection and large particles (> 2.5×10-6 m) are dominated by gravity. Ninety percent of small particles deposit within 1 mm of the pipe’s length and during 0.1 seconds, medium size particles require 115 mm and 17 seconds and large particles need 8 mm and 1.5 seconds.